2014
DOI: 10.1111/jtxs.12088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooking Methods on Textural Properties and Water‐Holding Capacity of Broiler Breast Meat Deboned at Various Postmortem Times

Abstract: The effects of oven‐baking (OB) and water‐cooking (WC) methods on the textural properties and water‐holding capacity (WHC) of broiler breast meat were investigated. A total of 1,008 broilers processed and deboned at nine different postmortem (0.25, 1.25, 2.0, 2.5, 3.0, 3.5, 4.0, 6.0 and 24.0 h) duration were cooked by two different cooking methods. Textural properties of cooked meat were predicted by the Meullenet–Owens razor shear method, descriptive analysis and consumer testing. Moisture and expressible moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
3
16
0
1
Order By: Relevance
“…Lovatt (2004) indicated that a comparatively higher thermal conductivity value (0.57 vs. 0.025 W/m/K) and surface heat transfer coefficient (100-200 vs. 5-10 W/m 2 /K) easily resulted in the heat transfer and heating of targets through water than through air. In this study, the cooking loss of WC native chicken meat was significantly lower than that of OC native chicken meat (P < 0.001), which agreed with previous studies (Zhuang & Savage 2008;Lee et al 2014) in which broiler chicken meats were evaluated. Therefore, in the current study, OC meat required more time to reach the same internal temperature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Lovatt (2004) indicated that a comparatively higher thermal conductivity value (0.57 vs. 0.025 W/m/K) and surface heat transfer coefficient (100-200 vs. 5-10 W/m 2 /K) easily resulted in the heat transfer and heating of targets through water than through air. In this study, the cooking loss of WC native chicken meat was significantly lower than that of OC native chicken meat (P < 0.001), which agreed with previous studies (Zhuang & Savage 2008;Lee et al 2014) in which broiler chicken meats were evaluated. Therefore, in the current study, OC meat required more time to reach the same internal temperature.…”
Section: Resultssupporting
confidence: 92%
“…weight loss, water-holding capacity modification, color and aroma development, and muscle fiber shrinkage) are highly dependent on the composition and characteristics of muscle tissues and heating methods as well as the time-temperature progress during cooking, which eventually influence the quality parameters and palatability of meat and meat products (Lee et al 2014;Chumngoen et al 2016a). weight loss, water-holding capacity modification, color and aroma development, and muscle fiber shrinkage) are highly dependent on the composition and characteristics of muscle tissues and heating methods as well as the time-temperature progress during cooking, which eventually influence the quality parameters and palatability of meat and meat products (Lee et al 2014;Chumngoen et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and endpoint meat temperatures are need to be closely followed as they may differ significantly for different cuts of meat. Cooking methods affect quality characteristics of meat like as yield, tenderness, juiciness, flavor and palatability by causing physical and biochemical changes in protein, carbohydrate, lipid and other minor components (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to the condition of food material and the intended purpose of use, it is categorized as a cooking type, a pasteurisation type or a packaging type (Díaz, Nieto, Garrido, & Bañón, 2008;Jang & Lee, 2005;Nyati, 2000). SV technique provides lots of benefits for foods such as extending the shelf life, producing tastier and juicier product, reducing heat-induced contaminants like heterocyclic aromatic amine in food products comparing to traditional methods (Armstrong & McIlveen, 2000;Lee, Xiong, Chang, Owens, & Meullenet, 2014;Oz & Zikirov, 2015;Wang, Chang, & Chen, 2004). The shelf-life prolonging effect of SV is mostly achieved by the inactivation of vegetative cells during the application of heat, or by prevention of aerobic bacterial growth and recontamination during storage thanks to its vacuum pack.…”
Section: Introductionmentioning
confidence: 99%